Case Study Of Court Decision Number 262/PDT.G/2020/PN.KPG Regarding Divorce Law Without Civil Registration Of The Marriage Certificate - Jonneri Bukit; Widia Maria Br Bukit (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
A marriage may be declared valid if it is performed in accordance with the tenets of the parties' respective religions and in accordance with Article 2(1) of Law No. 1 of 1974 on Marriage. The primary concerns of this study were: (1) the factors that judges must take into account in order to grant a divorce suit without a marriage certificate; and (2) the legal ramifications of the judge's decision to grant the divorce suit without a civil registration marriage certificate. The research method employed was the normative legal research method, which is essentially library research that examines document studies, employing various secondary legal materials such as statutory regulations and societally applicable legal norms, legal theory, scholarly opinions, and court decisions. By perusing the library's primary legal materials, secondary legal materials, and tertiary legal materials, a collection of legal materials was obtained. The findings of this study indicated that the judge's decision in a divorce case without a civil registration marriage certificate is based on the Plaintiff's documentary evidence and witness testimonies. In accordance with the provisions of Article 19 letters (b), (d), and (f) of Government Regulation Number 9 of 1975 concerning Implementation of Law Number 1 of 1974 concerning Marriage and Article 125 HIR/149 RBg, the divorce petition filed by the Plaintiff can be granted. The legal consequence for the parties is the dissolution of the relationship between the husband and wife, and the child will become a victim of the divorce.